Obraz obyczajowości seksualnej młodych kobiet i mężczyzn. Stosunek do wybranych norm związanych z aktywnością seksualną - Wąż, Krzysztof (Adult Education Discourses, 2020)
Nowadays, we can observe a fundamental change in the axionormative order related to human sexuality and a change in the role of individual agendas (factors) of sexual socialization. The study presents selected results of a study on the sexual morality of adolescents on the threshold of adulthood, aged 18-19, carried out on a nationwide research sample in 2017. The subject of the study was the attitude of the respondents to social norms related to sexual activity. Most respondents have had their first pre-initiation sexual experience, slightly more than half of the respondents have had their sexual initiation. More often, women have such experiences, which is one of the most important pieces of evidence in changes in the mores of young adults. Respondents support norms that can be described as components of liberal sexual customs. The sex of the respondents is an important factor in differentiating their views. Greater liberalism of young men is manifested, among others, in their relation to norms related to risky sexual behavior. Women significantly more often support norms that relate to sexual health.